Video Diversion During Fundoscopic Examination in Children: A Randomized Controlled Trial. (July 2014) - Singhal, Ash; Yang, Michael M.H.; Kerr, John M.
Fundoscopy is an important aspect of a neurological examination but can be challenging in uncooperative children. This study explored whether viewing a video during examination improves the success, duration, and ease of pediatric fundoscopy. This single-practitioner, randomized study involved 60 patients aged 1 to 8 years. Patients were randomized (by eye examined) to the treatment group (video-assisted) or control group (no video). A caregiver and the practitioner ranked the level of difficulty of each examination. There was a 28% improvement in the success rate of visualizing the optic disc ( P < .001). Further analysis showed a 48% improvement in the success rate in children aged 1 to 4 years ( P < .001) but no difference in children aged 5 to 8 years ( P = .23). Time needed to visualize the optic disc also improved (Δ16.3 s, P < .001). Improvement in the ease of examination ( P < .001) was noted by both the practitioner and caregiver. This simple adjunct has the potential to improve the efficacy of this aspect of the pediatric neurological examination.